Mineralisasi Nitrogen pada Komposisi Bahan Gambut dan Kotoran Ayam - Sukmawati Sukmawati; Fakhrur Razie; Abdul Haris (Acta Solum, 2022)
Peat soils contain high concentrations of organic nitrogen, but in a form that is not available to plants. South Kalimantan has NH4+ in the range 4.51- 736.86 mg.kg-1 and NO3- content is in the range of 0.37-54.69 mg.kg-1. The low availability of N nutrients in peatlands is due to the slow nitrogen mineralization process and the very high mobility of N in the soil. This study aims to determine the effect of the composition of peat and chicken manure on nitrogen mineralization. This study used a single factor in completely randomized design (CRD) with 5 treatments and 4 replications. carried out in greenhouses and in the Soil Laboratory of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The treatment is the composition of peat and chicken manure, namely 100% peat material, 80% peat material + 20% chicken manure, 60% peat material + 40% chicken manure, 40% peat material + 60% chicken manure, 20% peat material + 80% chicken manure. The best composition for nitrogen mineralization is based on the high nitrate content, which is found in the composition of 80% peat soil + 20% chicken manure in the first month of incubation, and on the composition of 80% peat soil + 20% chicken manure in the second month. This composition is the best composition from a combination of peat material and chicken manure against nitrogen mineralization in the form of nitrates.